2016
DOI: 10.1038/scsandc.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Subacute post-traumatic ascending myelopathy after T12 burst fracture in a 32-year-old male: case report and surgical result of cervical durotomy

Abstract: To draw attention to a rare neurological deterioration after spinal cord injury (SCI) and to discuss evidence supporting an increase in cerebrospinal fluid pressure (CSFP), we present an extremely rare case of subacute post-traumatic ascending myelopathy (SPAM) in which the patient sustained a T12 fracture initially resulting in paraplegia and after undergoing posterior fixation and anterior decompression. The patient was a 32-year-old healthy man who sustained a T12 burst fracture with complete paraplegia aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 18 publications
(22 reference statements)
0
20
0
Order By: Relevance
“…A lateral position is better for patients who are being monitored by Codman probe, but a ring-shaped pillow can also be used to support patients in a supine position to avoid increasing ISP. Increases in pressure can cause subacute posttraumatic ascending myelopathy [ 55 ]. In some instances, aggravated venous hypertension and/or arterial hypotension at the injury site and equivalent degrees of dural occlusion can cause loss of branch blood flow, which may lead to impaired spinal cord perfusion and can produce additional secondary injury [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lateral position is better for patients who are being monitored by Codman probe, but a ring-shaped pillow can also be used to support patients in a supine position to avoid increasing ISP. Increases in pressure can cause subacute posttraumatic ascending myelopathy [ 55 ]. In some instances, aggravated venous hypertension and/or arterial hypotension at the injury site and equivalent degrees of dural occlusion can cause loss of branch blood flow, which may lead to impaired spinal cord perfusion and can produce additional secondary injury [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surgical decompression was performed to reduce the increased CSF pressure with an attempt at SPAM resolution in 2 cases in accordance with the CSF flow alteration hypothesis in SPAM 12,18 . Yablon et al 28 suggested early surgical decompression after the initial SCI could prevent SPAM.…”
Section: Treatmentmentioning
confidence: 99%
“…Hence, we performed an extensive literature review for this entity and analyzed 23 published articles reporting SPAM to date 2,5-25 . Only 29 cases of SPAM in patients with thoracolumbar (TL) trauma were found.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we reviewed the existing literature on this rare entity to elucidate and analyze SPAM. We found only 28 cases of SPAM after thoracolumbar injury that were reported in the literature 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . We report a case of SPAM occurring after T11/12 fracture-dislocation with rapid ascent of neurological level with sudden worsening after surgery.…”
mentioning
confidence: 99%